UNDANG UNDANG NOMOR 3 TAHUN 2025 REVISI UNDANG UNDANG NOMOR 34 TAHUN 2004 TENTANG TENTARA NASIONAL INDONESIA DALAM PENDEKATAN INTERDISIPLINER - Bahrudin Salim (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to examine Law Number 3 of 2025, revision of Law Number 34 of 2004 concerning the Indonesian National Army with an interdisciplinary approach as a basis for recommendations for reformulation of the Law on the Indonesian National Army. This study is a literature study with qualitative methods and a descriptive analysis approach. The results of the study explain that after Law Number 3 of 2025, revision of Law Number 34 of 2004 was studied with an interdisciplinary approach, it was concluded that mandatory soldiers include the royal army, the keormasan army, the religious army, the Hizbullah army (BANSER), the kyai and santri army, defenders of the homeland, the people's security army, the people's security agency and the Indonesian people's army whose personnel and families participated in defending the country in physical and non physical wars, the need for digital technology-based defense equipment such as artificial intelligence, cyber space and robotics and the formation of a cyber force dimension to deal with cyber attacks. In addition, the law did not pass the philosophical, sociological and juridical test stages and was not relevant to the geopolitical conditions and the universal defense system which forced him to maintain professionalism by not conducting non-war military operations and not holding civil positions, therefore the constitutional court needs to annual the law and return it to the government and the people's representative council and encourage them to revise it again as the reformulation of the TNI law that the researcher conveyed.